Novel Hepatitic C Virus (HCV) Diagnosis and Treatment Delivery Systems: Facilitating HCV Elimination by Thinking Outside the Clinic. (27th November 2020) - Bajis, Sahar; Applegate, Tanya L; Grebely, Jason; Matthews, Gail V; Dore, Gregory J
Abstract: The World Health Organization has set a goal to eliminate hepatitis C virus (HCV) infection as public health threat by 2030. Although the advent of highly effective and tolerable direct-acting antiviral therapy has paved the way for HCV elimination, most people with HCV infection remain undiagnosed and untreated globally, with striking disparities between high-income and low- to middle-income countries. Novel decentralized and cost-effective "test-and-treat" strategies are critically needed to identify the millions of people unaware of their status and link them to treatment.